2013
DOI: 10.1002/anie.201300833
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Component Palladium‐Catalyzed Oxidative CC Coupling Reaction: A Domino Process in Two Dimensions

Abstract: In multicomponent reactions (MCRs), three or more reactants combine in a single chemical step to give a product that contains nearly all the atoms of the individual reactants. Compared with multistep reaction routes, MCRs are highly attractive in terms of step economy. [1,2] Typical MCRs proceed in a linear domino mode: in the first stage, the components A and B (Scheme 1 a) give rise to a reactive intermediate (AB) which then reacts with a third component (C), and so on, until the sequence is terminated. Very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 34 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Metal-catalyzed dehydrogenative β -C(sp 3 )–H functionalization reactions via dehydrogenative desaturation 28,29 were also amenable to esters 3034 , lactams 35 , and other substrates 3648 , demonstrating the ability of this type of reaction to rapidly construct complex molecule from simple substrates. Such reactions will continue to flourish in the future in view of the recent advance in the development of catalytic methods for generation of unsaturated compounds via dehydrogenation 3949 as well as the versatility of unsaturated compounds as synthetic intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-catalyzed dehydrogenative β -C(sp 3 )–H functionalization reactions via dehydrogenative desaturation 28,29 were also amenable to esters 3034 , lactams 35 , and other substrates 3648 , demonstrating the ability of this type of reaction to rapidly construct complex molecule from simple substrates. Such reactions will continue to flourish in the future in view of the recent advance in the development of catalytic methods for generation of unsaturated compounds via dehydrogenation 3949 as well as the versatility of unsaturated compounds as synthetic intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…The three-component coupling reaction of indoles 1, β-ketoesters 34 and arylboronicacids 111 via the regioselective palladium-catalyzed oxidative reaction was studied for the preparation of indole-based heterocycles 112 ( Scheme 49 ). 113 Indole coupled more rapidly than β-ketoester with the arylboronic acid, and this rate variation was important under the three-component reaction conditions, possibly because the coupling with β-ketoester involves an unstable enone intermediate.…”
Section: Multicomponent Reactions Of Indolesmentioning
confidence: 99%
“…(36)] close to those used in the absence of the third component [see Eqs (34) and (35)]. [73] Studies of two-component coupling experiments led to favor a domino reaction involving firstly the coupling between the indole and the arylboronate [74] and subsequent reaction of the resulting OHR product with the dehydrogenated -ketoester, as depicted in Scheme 9. Control experiments have nevertheless shown that the KTR-PHR product independently obtained from -ketoester/indole coupling (see Subchapter 6.2) reacts with the aryboronate to also afford the three-component product, but that would be, at the best, a minor reaction pathway under the three-component domino reactions conditions.…”
Section: Domino Ohr + Ktr + Phrmentioning
confidence: 92%